2021
DOI: 10.1109/jphot.2020.3048702
|View full text |Cite
|
Sign up to set email alerts
|

Reservoir Computing Based on Two Parallel Reservoirs Under Identical Electrical Message Injection

Abstract: In this work, we propose and numerically investigate a scheme for reservoir computing (RC) based on two parallel reservoirs under identical electrical message injection, in which two semiconductor lasers (SLs) under optical feedback are utilized as two parallel reservoirs. For simplifying the system, only one mask signal is employed in this scheme. After multiplying with input data, the masked information is injected into two parallel reservoir lasers (SL1 and SL2). The virtual node states can be obtained from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…To overcome this drawback, it is necessary and challenging to develop an integrated time-delayed P-RC system to solve more complex tasks. In 2021, Yue et al implemented a parallel delayed RC system based on two SLs using electronic injection technology, with an NMSE value below 0.03 and a data processing rate of 28 GSa/s . In 2023, Hou et al proposed the parallel reservoirs of the multiple RC used for handwritten digit recognition tasks, with a recognition accuracy of 0.978 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome this drawback, it is necessary and challenging to develop an integrated time-delayed P-RC system to solve more complex tasks. In 2021, Yue et al implemented a parallel delayed RC system based on two SLs using electronic injection technology, with an NMSE value below 0.03 and a data processing rate of 28 GSa/s . In 2023, Hou et al proposed the parallel reservoirs of the multiple RC used for handwritten digit recognition tasks, with a recognition accuracy of 0.978 .…”
Section: Introductionmentioning
confidence: 99%
“…In 2021, Yue et al implemented a parallel delayed RC system based on two SLs using electronic injection technology, with an NMSE value below 0.03 and a data processing rate of 28 GSa/s. 36 In 2023, Hou et al proposed the parallel reservoirs of the multiple RC used for handwritten digit recognition tasks, with a recognition accuracy of 0.978. 37 Subsequently, Zhong et al have demonstrated a P-RC system with three laterally coupled lasers that could reproduce the nonlinear dynamics 38 In 2023, Zou et al proposed a nonfeedback method that utilized the pulse broadening effect induced by optical dispersion to implement a reservior layer by computing the multiplication of the modulator with the summation of the pulse temporal integration of the distributed feedback-laser diode.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the above methods in this scenario, the advantages of the reservoir computing (RC) only training output weights via linear regression algorithm and randomly fixing connection weights to simplify the learning algorithm with lower calculation consumption and faster learning process are relatively prominent [ 19 21 ]. Furthermore, RC is applicable for hardware implementations with its robustness against fabrication tolerances, and RC has demonstrated advanced property on a series of complicated assignments with time-dependent data [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the above methods in this scenario, the advantages of the reservoir computing (RC) only training output weights via linear regression algorithm and randomly fixing connection weights to simplify the learning algorithm are relatively prominent [19][20][21]. Furthermore, RC is applicable for hardware implementations with its robustness against fabrication tolerances, and RC has demonstrated advanced property on a series of complicated assignments with time-dependent data [22].…”
Section: Introductionmentioning
confidence: 99%